"Who Should Be the Next CEO?" Desirable Successor Characteristics in Recovery from Financial Distress. Issue 15 (8th December 2021) - Yao, Shanshan
ABSTRACT: The goal of this study is to understand which characteristics of CEO successors are most desirable in the recovery from financial distress. Using a sample of 316 non-financial firms experienced "special treatment" regulations with CEO turnover in China from 2002 to 2018, the results demonstrate that CEO experience and political connections have significant influence and can substitute for each other in the recovery process, while the effects of education background, finance experience, and banking relationships are insignificant. Finally, government subsidies play a partial mediating role between guanxi resources and recovery from financial distress.